Razvlekatelʹnyj diskurs v russkoâzyčnom internete - Кarpova, Tat’âna B. (Stylistyka, 2021)
Leisure discourse is one of the main types of the d course of Russian-speaking internet. It realizes the aims of a language person for the way of spending time, resting, entertain- ment. The field of leisure discourse in runet is formed by such micro-fields as communi cation, self-presentation (designing of a web-person), сгеапѵе works, hobby, cognition (navigation), playing, sex. Motives and functions of leisure activity of a language person, as well as those genre forms where this activity takes place, have been analyzed